Identification of Gram Negative Bacteria in the Urine of Catheterized Patients at Referral Hospital in Ternate - Waraningsih, Septiana; Do Toka, Wahyunita; Dahlan, Muhammad; Rachman, Ismail (Jurnal Kedokteran Brawijaya, 2024)
Infections can occur anywhere and often occur usually sourced from hospitals. Nosocomial infection is an infection caused by various microorganisms, one of which is bacteria originating from the hospital environment. Gram-negative bacteria, especially the Enterobacteriaceae family, are the main bacteria that cause nosocomial infections. One of the common infectious diseases in health care is urinary tract infection and some UTIs are caused by catheter insertion. This research aimed to identify gram-negative bacteria in the urine of catheterized patients at RSUD Dr. H. Chasan Boesoirie, a referral hospital in Ternate. The research method is descriptive observational with a cross sectional approach using a total sampling technique obtained 83 samples from November 14, 2023 to December 17, 2023. The results showed that 7 samples (8.4%) were identified as positive for gram-negative bacteria with 7 types of bacterial species and the highest percentage of bacteria was Escherichia coli (33.4%). The use of urinary catheters was mostly female (55.4%) with the highest age in the age group 56-65 years (34.9%) and the duration of urinary catheter use was mostly in samples with a duration of <72 hours (90.4%). In conclusion, gram-negative bacteria were identified in the urine of catheterized patients.